SEDIMENT TRANSPORT STUDY ON BELITUNG ISLAND DUE TO DREDGING ACTIVITY - Dwinanda, Dhira
Dredging is one of the methods used for extracting resources that is found in coastal areas and in the ocean. This study is aiming to make model of ocean current and sediment transport that occurs at the East Coast of Belitung Island. The goal of this study is observing how dredging activity affects sedimentation and erosion process at East Belitung and determining whether the dredging can be done or not. Hydrodinamic modeling with Delft3D software will be done in this research. There will be 3 major parts in the modeling process, and they are big domain modeling, small domain modeling and sedimentation modeling. Big domain modeling yield tidal water level validation of 4.92% for 5 location and water level used for boundary condition for small domain modeling. Small domain modeling yield tidal water level validation of 4.77% and current velocity validation of 28.33%. Current validation shows that the current generated from the model and the current from field observation have the same phase although the amplitude is relatively smaller. Sedimentation model of existing condition and 3 condition of dredging shows that there is no sedimentation and erosion happening at the East Coast of Belitung Island. Sedimentation process take place 15 – 20 kilometers away from the coast. The maximum sedimentation that occurs is 0.08 meters and the maximum erosion that occurs is 0.6 meters. Dredging also affects the current velocity in the area and also the sedimentation process near the dredging area. The time frame used for modeling which is 1 month is deemed to be to short and haven’t shown significant changes on the sedimentation process. It is concluded that it is necessary to have longer modeling time, and that is more than a year.